2018
DOI: 10.23876/j.krcp.2018.37.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Uremic pruritus and associated factors in hemodialysis patients: A multi-center study

Abstract: BackgroundUremic pruritus is a common and disturbing problem in hemodialysis patients. Although its pathogenesis is not completely understood, it is thought to be multifactorial. The aim of this study was to identify risk factors of uremic pruritus in hemodialysis patients.MethodsA total of 249 patients from four dialysis centers were included in this study. Data were collected using a questionnaire, the visual analogue scale, and the Hospital Anxiety and Depression Scale. We investigated whether socio-demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 30 publications
2
57
0
13
Order By: Relevance
“…The results are important and agree with another study conducted in Pakistan [22]. Our study indicates that age, hemodialysis years, and timing of dialysis session had no significant association with 5-D scores, which is in agreement with previous studies [20,23].…”
Section: Discussionsupporting
confidence: 93%
“…The results are important and agree with another study conducted in Pakistan [22]. Our study indicates that age, hemodialysis years, and timing of dialysis session had no significant association with 5-D scores, which is in agreement with previous studies [20,23].…”
Section: Discussionsupporting
confidence: 93%
“…Yet another study in Pakistan reported almost similar patterns of pruritus severity with 50%, 28%, and 14% of respondents having mild, moderate, and severe pruritus, respectively [35]. Other cross-sectional studies in Turkey also showed a high prevalence of 85.4% [36], and 53.4% [37], respectively. However, 50.4% of patients experienced moderate pruritus, and pruritus led to sleep disturbances in 33.8% of patients [37].…”
Section: Discussionmentioning
confidence: 86%
“…Other cross-sectional studies in Turkey also showed a high prevalence of 85.4% [36], and 53.4% [37], respectively. However, 50.4% of patients experienced moderate pruritus, and pruritus led to sleep disturbances in 33.8% of patients [37]. In our study, a longer duration of CKD and hemodialysis had a very negligible effect on pruritus, which differs from another study in which a duration of hemodialysis of more than 2 years resulted in higher rates of pruritus (75% vs 25%) compared to those doing hemodialysis for less than 2 years [38].…”
Section: Discussionmentioning
confidence: 94%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ A previous large study showed that approximately 42% of patients with HD experience moderate to extreme pruritus 29 . Severe uremic pruritus may cause deteriorating QOL and poor clinical outcomes in chronic HD patients 30,31 . Reasons for the occurrence of pruritus remain unknown, but the possibility of an association of uremic pruritus with middle molecules such as β2-microglobulin has been reported; therefore, the increased clearance of middle molecules may help reduce uremic pruritus 32,33 .…”
Section: Discussionmentioning
confidence: 99%